2011
DOI: 10.1007/s00482-011-1057-9
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of dropout rates in randomized controlled clinical trials

Abstract: In spite of analgesic effects, many osteoarthritis patients prefer to stop chronic opioid use, because of adverse events. Therefore, opioids are not generally recommended in osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
3
10
0
1
Order By: Relevance
“…49 Long-term follow-up has been associated with increased dropout rate. 50 Apart from the relatively high dropout rate that might be encountered in chronic pain studies, 51 RCTs evaluating anaesthetic interventions tend to have short follow-up periods. This could account for the relatively low (4.6%) observed attrition rate in the present systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…49 Long-term follow-up has been associated with increased dropout rate. 50 Apart from the relatively high dropout rate that might be encountered in chronic pain studies, 51 RCTs evaluating anaesthetic interventions tend to have short follow-up periods. This could account for the relatively low (4.6%) observed attrition rate in the present systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for the negative attitude towards tramadol could be the high prevalence of side effects [22,23], which may result to therapy switching or discontinuation, and thus a negative evaluation of its effectiveness by GPs [24,25]. Furthermore, the GPs’ negative attitudes towards the effectiveness of topical NSAIDs, glucosamine, and hyaluronic acid intra-articular injections might be explained by the discrepancies between the recommendations of the SCS and the Dutch NHG-standard for non-traumatic knee complaints in adults [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have described rates of therapy discontinuation and switching among OA patients, but these have mainly been among patients initiated on NS‐NSAIDs and Cox‐2s, 38–40 data on other recommended OA therapies are lacking. More recently, a meta‐analysis evaluating discontinuation because of loss of efficacy or adverse events associated with opioid therapy in clinical trials of OA patients reported that the significantly greater discontinuation rate with opioids relative to placebo (odds ratio 1.3; 95% confidence interval 1.2 to 1.4) was primarily related to adverse events 41 . However, controlled clinical trials are often not representative of general clinical practice.…”
Section: Introductionmentioning
confidence: 99%